Research on EMI Noise Suppression of Zeta Converter Based on Chaotic Spread Spectrum - Yifei Sun; Tengfei Liu; Xuejun Zong; Kan He; Lian Lian; Feng Jiang (IEEE Access)
High-frequency switching in power converters, characterized by rapid voltage and current fluctuations, is primary source of Electromagnetic interference (EMI) noise. This study proposes a novel four-dimensional chaotic circuit as a modulation signal for spread spectrum circuit in the control stage of a Zeta converter to mitigate EMI. The research methodology involves modeling the Zeta converter and analyzing system stability, followed by the design of a new four-dimensional chaotic circuit. The chaotic signal generated by this circuit serves as the modulation signal, implementing chaotic spread spectrum modulation technology to suppress EMI noise in the Zeta converter. To validate the proposed theoretical analysis, the converter is studied using a time-domain circuit simulation software, it shows that this method achieves EMI noise suppression exceeding 10 dB compared to a Zeta converter without chaotic spread spectrum technology. Experiments on a prototype circuit confirm theoretical results.